Clinical practice guidelines for hepatocellular carcinoma: The Japan Society of Hepatology 2017 (4th JSH‐HCC guidelines) 2019 update. Issue 10 (6th September 2019) - Kokudo, Norihiro; Takemura, Nobuyuki; Hasegawa, Kiyoshi; Takayama, Tadatoshi; Kubo, Shoji; Shimada, Mitsuo; Nagano, Hiroaki; Hatano, Etsuro; Izumi, Namiki; Kaneko, Shuichi; Kudo, Masatoshi; Iijima, Hiroko; et al.
Abstract : The fourth version of Clinical Practice Guidelines for Hepatocellular Carcinoma was revised by the Japan Society of Hepatology, according to the methodology of evidence‐based medicine and partly to the Grading of Recommendations Assessment, Development, and Evaluation system, which was published in October 2017 in Japanese. New or revised recommendations were described, herein, with a special reference to the surveillance, diagnostic, and treatment algorithms.